Empirical modelling of vibration in micro end milling of PMMA - Ali, Mohammad Yeakub; Mohamed, Abd. Rahman; Khan, Ahsan Ali; Asfana, Banu; Lutfi, M.; Fahmi, M. I. (IDOSI Publication, 2013)
This paper presents the vibration issue in micro end milling of of poly methyl methacrylate (PMMA) workpiece using integrated multi-process machine tools DT 110 (Mikrotools Inc., Singapore) with control parameter; spindle speed, feed rate and depth of cut. The vibration was measured using accelerometer (DYTRAN Instruments Inc., USA). The optimum solution for minimum average vibrationis 64.3 Hz with spindle speed 2500 rpm, feed rate 2 mm/min and depth of cut 1.5 ìm. These micro end milling parameters are suitable to machine PMMA to get high precision. The analysis revealed that compared to spindle speed; the feed rate and depth of cut have highest influence on vibration during machining process.